(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Summary: Ethnic variations exist in the relationship of adiposity indices with metabolic syndrome (MetS). There are however, limited studies on the usefulness of body adiposity index (BAI) and visceral adiposity index (VAI) among Hausas of Kano, Northern Nigeria. The aim of the study was to determine the relationship of measures of adiposity to the components of MetS in Hausas of Kano. The study included 465 (266 males and 199 females) subjects, with mean age of 34.4 years and 32.0 years for males and females respectively. Anthropometric measures were obtained using standard protocols. Visceral adiposity was estimated using sex specific VAI. Fasting blood sample was obtained for serum analyses of lipid profiles, glucose, protein and uric acid. Pearson’s correlation was used to test the association between adiposity measures with MetS indices while Student’s t test was used for group comparison. The results of the study showed that the adiposity indices significantly correlate with metabolic syndrome indices. Visceral adiposity index was superior to other adiposity measures and Waist to hip ratio was the strongest anthropometric correlate of MetS components. In conclusion, WHR is the strongest anthropometric correlate of MetS components. Body adiposity index, NC and HC are weaker adiposity tools. Visceral adiposity index is superior to all other adiposity tools.